Proper Names in Poetic Translations by Viktor Voroshilsky - Bednarczyk, Anna (W kręgu zagadnień języka, literatury i kultury: Księga jubileuszowa dedykowana Profesorowi Jarosławowi Wierzbińskiemu, 2022)
The aim of this research is to expose Wiktor Voroshilsky’s translation strategy, especially the translation methods and techniques he uses as the author of the Polish versions of Russian poems. Theorists of translation quite often pay attention to the problem of translation of proper names, exploring different contexts related to this issue. Bazyli Tichoniuk wrote about the translation of names within Polish and Russian at the time, while for other languages we can mention works by Ewa Teodorowicz-Hellman, Anna Szcześniak, Elżbieta Skibińska, Anna Majkiewicz, and Krzysztof Hejwowski.This article attempts to indicate a specific translator’s approach to translating proper names. The material under study consists of 25 poems selected from 211 works translated by Voroshilsky. The main selection criterion was the saturation of the poem with elements of interest to the authors, as well as their diversity. This determined the research method, which focused on analysing the repeatability and variety of translation techniques.Finally, we concluded that Voroshilsky employed different methods of translation, often guided by the function performed by the proper names in the text. We also paid attention to his objective to bring the text closer to the target audience and on the creativity of the translator.